The Structure of Nominal Phraseological Units of English, Russian and Uzbek Languages - Alisherovna, Mavlonova Nargiza; Ulugbekovna, Negmatova Mukarram (Journal of Innovation in Education and Social Research, 2024)
This research is aimed at a comparative study of nominal phraseological units of English, Russian, Uzbek languages. Nominal phraseological units are phrases or expressions that consist of two or more words that, when combined, create a different meaning from the literal definitions of its individual words. Nominal phraseological units in Russian and Uzbek languages add cultural depth and vividness to the languages, embodying traditional values and expressions. A nominal group is widely regarded as synonymous with noun phrase in other grammatical models. Nominal phraseological units (NPUs) in the English language are multi-word expressions or fixed phrases centered around a noun. They convey a meaning that is not directly inferred from the meanings of their individual words. These units are common in English and often have idiomatic or figurative meanings.